People won, now what? The role of civil society organizations in anti-corruption and judicial reform in post-uprising Armenia (2018–2025) - Paturyan, Yevgenya Jenny; Simonyan, Liana; Papikyan, Gor (Frontiers in Political Science, 2025)
In 2018, a mass uprising, known as the Velvet Revolution, ousted an unpopular semi-authoritarian government in Armenia. The new government vowed rapid democratization through ambitious reforms. Key civil society actors enthusiastically supported the shift in the political atmosphere, embracing the post-uprising window of opportunity to engage with the new government and push for democratic consolidation in their respective areas of expertise. This paper examines anti-corruption and judicial reforms in post-revolutionary Armenia, focusing on the role of civil society actors in maintaining the pro-democratic momentum. The paper investigates the following research question: “What was the role of civil society organizations in anti-corruption and judicial reforms in Armenia after the 2018 Velvet Revolution?” We rely on document analysis and qualitative interviews with civil society representatives, policy experts and government officials to argue that the strength of civil society and availability of allies partially explain the differences in anti-corruption and judicial reform processes and outcomes. In the anti-corruption case, the main actors (the government, prominent civil society organizations, and the EU) were more or less “on the same page.” In the case of the judicial reform, there were strong divisions of opinion among civil society organizations, local and international experts. The findings contribute to broader understanding of the role of civil society in the early years of democratic transition.